1980
DOI: 10.1111/j.1939-0025.1980.tb03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and involuntary treatment.

Abstract: iscussions of involuntary treatment D in the psychiatric literature have not systematically examined patients' opinions about their treatment. Psychiatrists frequently discuss appreciative patients who describe their involuntary treatment as very helpful. However, these anecdotal reports are dismissed as self-serving by those who question the benefits of involunta.ry treatment. Recent criticisms of involuntary treatment in the legal literature emphasize the lack of evidence for benefits 1 , s . 5 and conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 7 publications
(1 reference statement)
1
17
1
Order By: Relevance
“…This may be the reason why patients, in retrospect, considered the measure to have been justified and useful. Similar findings have been made in psychotic patients who were committed to psychiatric hospitalization and involuntarily treated with anti-psychotic medications [7][8][9]. This assumption is also emphasized by reported findings showing that committed patients do have a similar and sometimes even better level of adherence to treatment than other patients [10, 12-14, 16, 17].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This may be the reason why patients, in retrospect, considered the measure to have been justified and useful. Similar findings have been made in psychotic patients who were committed to psychiatric hospitalization and involuntarily treated with anti-psychotic medications [7][8][9]. This assumption is also emphasized by reported findings showing that committed patients do have a similar and sometimes even better level of adherence to treatment than other patients [10, 12-14, 16, 17].…”
Section: Discussionsupporting
confidence: 68%
“…medication) has been supported by decisions of many civil courts [1], while several scientific studies have demonstrated that clinical decisions to commit and treat psychotic patients are highly reproducible and clinically sound across psychiatrists [4][5][6]. Moreover, patients' retrospective opinions about commitment and involuntary treatment generally support the usefulness of these practices [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…We must remember that recent research has shown that most commitment patients are helped, not hurt, by the system. Furthermore, although they were hospitalized against their will, in retrospect most had positive feelings about their hospitalization experience (Goove and Fain 1977;Spensley , Edwards, and White 1980). Finally, the duration of involuntary treatment has been shown to be generally brief, and a significant proportion of these patients continue to participate in treatment voluntarily afterwards (Goove and Fain 1977;Spensley , Barterm, and Werner 1974;Tomerlleri, Lakshminarayanam, and Herjanic 1977).…”
Section: Discussionmentioning
confidence: 93%
“…While there is still a debate concerning the optimal length of hospitalization for suicidal patients, research findings indicate that after hospitalization many committed psychiatric patients show improvement in their interpersonal relationships and evaluate their hospital stay positively (Goove and Fain 1977;Spensley, Edwards, and White 1980). In a study comparing the experiences of voluntary and committed psychiatric patients, Goove and Fain (1977) observe that one year after discharge from the hospital, both groups of patients reported a significant improvement in their relationships with their spouses and others.…”
Section: Siege2 and Tucker Suicide And Civil Commitment 351mentioning
confidence: 93%
“…All have reported generally positive views. Excandidates tend to be no different than voluntary patients in seeing their hospitalization experience as helpful and necessary (Edelsohn and Hiday, 1987;Kane et al, 1983;Spensley et al, 1980;Towes et al, 1981;Srenevasan et al, 1980;Tomelleri et al, 1977;Wood et al, 1984). Most of these studies, however, are marred by sampling problems.…”
Section: Outcomementioning
confidence: 95%